Cancer chemoprevention study of luffa aegyptiaca (sponge gourd) seed extract on human breast cancer cell lines (MCF-7) - Hassan, Habibah; Razali, Shakirah; Firus Khan, Al'aina Yuhainis; K Jalal, Tara; Salleh, Azil; Khatib, Alfi; Hashim, Ridzwan; Abdul Wahab, Ridhwan (2016)
Natural products from plant have been used for centuries to prevent various diseases including cancer. Many chemopreventive agents are believed to inhibit or delay the progression of cancer cells through suppression of cell proliferation, induction of apoptosis and cell cycle arrest. In Malaysia, breast cancer is the most common form of cancer affecting women. The prognosis for breast cancer is still poor and conventional treatment is not always effective. Therefore, this study aims to determine the chemopreventive effect of Luffa aegyptiaca seed extract (LSE) on breast cancer through anti-proliferative effect and its mechanisms on breast cancer cell (MCF-7) as evidenced by the result of IC50 determination, cell proliferation assay and flow cytometer analysis on apoptosis induction and cell cycle arrest. MCF-7 cells were plated at a density of 4.7 x 104 cells/ml in 6–well plate. Trypan blue exclusion method was used to determine cell viability. Untreated and LSE-treated MCF-7 cells were observed for morphological changes with an inverted-phase contrast microscope. The induction of apoptosis and cell cycle arrest was analysed using flow cytometry. LSE showed growth inhibitory effect with IC50 value at 0.0625 mg/ml. Moreover, LSE, show no toxic effect on normal cells possibly showing that it is a potential chemopreventive agent on MCF-7 via the induction of apoptosis and cell cycle arrest. Overall, the data collected provides new insight for the use of Luffa aegyptiaca seed as a chmopreventive agent on MCF-7. Keywords: Luffa aegyptiaca; anti-proliferative effect; apoptosis; cell cycle; MCF-7